Captive breeding and developmental biology of Sahyadria denisonii (Day 1865) (Cyprinidae), an endangered fish of the Western Ghats, India - Anna Mercy, T. V.; Sajan, S.; Malika, V. (Indian Journal of Fisheries, 2015)
Over the past few decades wild population of Sahyadria denisonii (Day 1865), an endemic ornamental barb of the Western Ghats of India has been overexploited for aquarium trade and is presently listed under endangered (EN) category in the IUCN Red List. The present study communicates the first ever success of captive breeding and early developmental studies of S. denisonii. Life history phases of S. denisonii were classified into embryonic, larval, juvenile, subadult and adult stages. Spawning season was from November to March in wild and fecundity varied depending on the size and age of breeding pairs. Eggs were obtained through induced breeding using ovaprim hormone at 0.4 ml per kg body weight. Fertilised eggs were adhesive, demersal and attached to any substratum having a diameter of 1184-1312 µm. Hatching took place 36 h after fertilisation at a water temperature of 27.5±0.5ºC. At hatching, mean larval length was 3.5±0.2 mm with high amount of yolk and the yolk sac remained up to 3-4 days. Organogenesis of larvae was completed 15-20 days after hatching. In this paper full developmental sequence from egg to adult stages of S. denisonii in controlled condition is described.